중심장액맥락망막병증에서 브롬페낙 점안 시 1년간 임상 경과 - 권미선(Mi Sun Kwon); 김유민(Yu Min Kim); 김진영(Jin Young Kim); 도재록(Jae Rock Do); 강용구(Yong Koo Kang); 박동호(Dong Ho Park) (Daihan angwa haghoi jabji, 2024)
목적: 중심장액맥락망막병증 환자에서 브롬페낙 점안액을 사용하였을 때의 1년간 임상 경과에 대해 보고하고자 한다. 대상과 방법: 중심장액맥락망막병증을 진단받고 1년 이상 경과 관찰이 가능하였던 57명(57안)의 의무기록을 후향적으로 분석하였다. 브롬페낙 점안액을 하루 2회 사용한 브롬페낙군(29안)과 사용하지 않은 대조군(28안)으로 나누었으며 1, 3, 6, 9, 12개월에 최대교정시력, 중심황반두께, 망막하액의 높이를 조사하였다. 또한 각 군에서 6개월 이상 망막하액이 지속되어 만성으로 분류된 환자의 비율을 비교하였다. 결과: 중심황반두께는 브롬페낙군과 대조군 모두 1개월째부터 초기보다 유의하게 호전되었으며(p=0.002, <0.001), 브롬페낙군이 대조군에 비해 6, 9, 12개월째에 유의하게 작았다(p=0.045, 0.042, 0.023). 망막하액의 높이는 두 군 모두 1개월째부터 초기보다 유의하게 감소하였으며(각각 p<0.001), 브롬페낙군이 대조군보다 6, 9, 12개월째 유의하게 작았다(p=0.037, 0.048, 0.046). 만성 중심장액맥락망막병증 환자의 비율은 브롬페낙군이 대조군보다 작았다(17.2% vs. 42.9%, p=0.035). 1년간 브롬페낙 점안으로 인한 각막 합병증은 보이지 않았다. 결론: 중심장액맥락망막병증 환자에서 1년간 브롬페낙 점안 시 만성으로의 진행 빈도가 감소하고 6개월 이후 유의한 해부학적 호전을 보여 향후 유용한 치료법 중 하나라고 생각된다. Purpose: To evaluate the efficacy of topical bromfenac in treating central serous chorioretinopathy (CSC) over a 1-year period. Methods: A retrospective analysis was conducted on 57 patients (57 eyes) with CSC followed for > 1 year. Patients were divided into two groups: those treated with bromfenac eye drops twice daily (29 eyes) and a control group (28 eyes). Best-corrected visual acuity (BCVA), central macular thickness (CMT), and subretinal fluid (SRF) height were measured and compared between the two groups as was the proportion of chronic cases. Results: Significant improvements in CMT and SRF height were noted in both groups over the follow-up period. The bromfenac group demonstrated significantly lower CMT at 6, 9, and 12 months (p = 0.045, 0.042, and 0.023, respectively) and lower SRF height (p = 0.037, 0.048, and 0.046, respectively) compared to the control group. The proportion of chronic cases was significantly lower in the bromfenac group (17.2%) compared to the control group (42.9%, p = 0.035). Conclusions: Topical bromfenac reduced the rate of progression to chronic CSC and showed significant anatomical improvements after 6 months, suggesting its potential as an effective treatment option. KCI Citation Count: 0